The Effect of Optimal Tax Revenue Utilization on Bridging Infrastructural Deficits in Nigeria: Empirical Evidence of South West Nigeria - Ajayi-Owoeye, Ayooluwa Olotu; Ajala, Michael Oludare Oladiran; Aguguom, Theophilus Anaekenwa; Otitolaiye, Emmanuel Dare (International Review of Management and Marketing, 2026)
Bridging infrastructural deficits remains a critical investment pathway for emerging economies in achieving sustainable growth. However, studies linking optimal tax revenue utilization to bridging infrastructural deficits (BIDs) are limited in developing countries, particularly Nigeria. This study seeks to fill this gap by examining the effect of optimal tax revenue utilization on infrastructural development in South West Nigeria. The study adopted a survey research design and employed a structured questionnaire administered to taxpayers across the six states of the region. Using Taro Yamane formula, a sample size of 400 respondents was determined. The validity and reliability of the instrument were confirmed through Cronbach Alpha, KMO, and Bartlett tests. A total of 98.5% of the questionnaires distributed via Google platform were retrieved and validated for analysis. Descriptive statistics revealed that most respondents agreed that optimal tax revenue utilization positively influences BIDs. Regression analysis further showed a significant joint effect of optimal tax revenue utilization on BIDs. The study concluded that effective utilization of tax revenue enhances infrastructural development in South West Nigeria. This paper contributes novel evidence by demonstrating the role of tax revenue optimization in reducing infrastructural gaps and creating investment opportunities in emerging economies like Nigeria.